(untitled) (MAUSAM, 1984)
Three cases when a pair of cyclonic storms interacted with each other have been presented and discussed in this paper. During the interacting phase, the storms moved temporarily in a clockwise manner around a common centre which is reverse of what is postulated in the well known Fujiwhara Effect. A explanation for this unusual movement has been attempted.